Pneumatosis cystoides intestinalis revealed after a hand-to-hand aggression: A case report. (2019) - Belkhir, A.; Jrad, M.; Sebei, A.; Soudani, M.; Haddad, A.; Boukriba, S.; Frikha, W.; Mizouni, H.
Highlights: Pneumatosis cystoides intestinalis should be interpreted with relevance to the entire clinical context. Positive diagnosis can be established by computed tomography imaging. Management of PCI is conditioned by the clinical and radiological presentation which is essentially related to the primary cause. Surgical procedure is required when suspecting transmural ischemia or bowel perforation. Abstract: Introduction: Pneumatosis cystoides intestinalis (PCI) is a condition defined by the presence of multiple gas-filled cysts within the intestinal wall. We demonstrated a case of PCI presenting as pneumoperitoneum following a hand-to-hand aggression. Consent was obtained from the patient for publication of this paper. Presentation of the case: This article describes a case of an 28 year-old man with medical history of gastroduodenal ulcer admitted in the emergency room with an acute abdominal pain secondary to a hand-to-hand aggression. Computed tomography (CT-scan) revealed signs of PCI, the presence of pneumoperitoneum and a small amount of fluid in the Douglas pouch. The patient underwent an urgent laparotomy in front of a high suspicion of a bowel perforation. Per operative findings revealed multiple small cysts of the terminal ileum and there were no bowel perforation. Discussion: Pneumatosis cystoides intestinalis may be related to a wide spectrum of gastrointestinal conditions. The diagnosis of PCI can be established by endoscopic ultrasound or CT-scan imaging. Management of PCI is conditioned by the clinical and radiological presentation which is essentially related to the primary cause. Conservative approach is allowed in a stable patient with no signs of complications. In the presence of predictive factors of pathologic PCI, namely transmural ischemia and bowel perforation, surgical operation is required. Conclusion: The management of PCI may be challenging particularly in the presence of pneumoperitoneum. Complications must be excluded before considering a conservative therapy. Therefore, PCI should be interpreted with relevance to the entire clinical context.